2007
DOI: 10.1016/j.pain.2006.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Preferential block of inactivation-deficient Na+ currents by capsaicin reveals a non-TRPV1 receptor within the Na+ channel

Abstract: Capsaicin elicits burning pain via the activation of the vanilloid receptor (TRPV1). Intriguingly, several reports showed that capsaicin also inhibits Na + currents but the mechanisms remain unclear. To explore this non-TRPV1 action we applied capsaicin to HEK293 cells stably expressing inactivation-deficient rat skeletal muscle Na + mutant channels (rNav1.4-WCW). Capsaicin elicited a conspicuous time-dependent block of inactivation-deficient Na + currents. The 50% inhibitory concentration (IC 50 ) of capsaici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 35 publications
(48 reference statements)
1
27
0
Order By: Relevance
“…It is still possible that our findings are non‐TRP channel mediated because TRP agonists exert other effects. For example, both TRPV1 and TRPA1 agonists can inhibit voltage‐gated sodium channels, which could be another avenue through which muscle cramping is attenuated. However, oral consumption of TRP agonists in the amount employed in this study does not significantly increase plasma concentration of these agonists, supporting the assertion that the effects of TRP agonists are reflexive in nature.…”
Section: Discussionmentioning
confidence: 99%
“…It is still possible that our findings are non‐TRP channel mediated because TRP agonists exert other effects. For example, both TRPV1 and TRPA1 agonists can inhibit voltage‐gated sodium channels, which could be another avenue through which muscle cramping is attenuated. However, oral consumption of TRP agonists in the amount employed in this study does not significantly increase plasma concentration of these agonists, supporting the assertion that the effects of TRP agonists are reflexive in nature.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that a drug-induced use-dependent block is attributed to the drug binding to a specific channel state (to the channel open stage, or to the inactivated state, thereby stabling the nonconducting channel state) (Savio-Galimberti et al 2012; Takeda et al 2006). Use-dependent block of capsaicin (30 µM) in neuronal Na + channels is related to direct capsaicin binding via non-TRPV1 receptor within the open Na + channel (Wang et al 2007). It is not known whether there is a non-TRPV1 receptor of capsaicin within open K + channels.…”
Section: Discussionmentioning
confidence: 99%
“…Voltage-clamp experiments showed that capsaicin inhibits Na + currents in specific types of ganglion neurons (46, 47). This effect might be related to TRPV1 or be independent of it, via changes in membrane elasticity (48) or via a non-TRPV1 receptor (49). Conduction blockade could be also associated with many other mechanisms of action demonstrated by vanilloid agonists (for example, insufficient energy supply due to mitochondrial dysfunction or inhibition of axonal transport).…”
Section: Conduction Analgesia With Vanilloid Agonistsmentioning
confidence: 99%